2019
DOI: 10.1038/s41391-019-0196-4
|View full text |Cite
|
Sign up to set email alerts
|

Transperineal laser ablation for percutaneous treatment of benign prostatic hyperplasia: a feasibility study. Results at 6 and 12 months from a retrospective multi-centric study

Abstract: Purpose To investigate the effectiveness and safety of SoracteLite™-transperineal percutaneous laser ablation (TPLA) in the treatment of patients with symptomatic benign prostatic hyperplasia (BPH) at 6 and 12 months follow-up. Methods Patients with urinary symptoms secondary to BPH underwent TPLA under local anesthesia in four centers. Under US guidance, up to four 21G applicators were inserted in the prostatic tissue. Each treatment was performed with diode laser operating at 1064 nm changing the illuminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 44 publications
2
69
0
Order By: Relevance
“…Using very thin applicators and high-precision energy delivery, percutaneous laser ablation has been demonstrated to be safe and effective ( 45 48 ). Several preliminary studies including short-term follow-up proved its feasibility, Pacella revealed IPSS improved from 22.5 ± 5.1 to 7.7 ± 3.3 at 6 months and 7.0 ± 2.9 at 12 months, Cai HJ proved ultrasound guided TPLA effective and safe with the QoL improved from 4.9 ± 1.7 to 2.3 ± 1.3 and the Qmax improved from 8.5 ± 3.0 to 15.2 ± 4.8 mL/s at 6 months after the procedure ( 37 , 41 ). However, no comparison with patients treated with other techniques has been performed, especially TURP, the most widely used surgical method and “gold standard” for BPH patients.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Using very thin applicators and high-precision energy delivery, percutaneous laser ablation has been demonstrated to be safe and effective ( 45 48 ). Several preliminary studies including short-term follow-up proved its feasibility, Pacella revealed IPSS improved from 22.5 ± 5.1 to 7.7 ± 3.3 at 6 months and 7.0 ± 2.9 at 12 months, Cai HJ proved ultrasound guided TPLA effective and safe with the QoL improved from 4.9 ± 1.7 to 2.3 ± 1.3 and the Qmax improved from 8.5 ± 3.0 to 15.2 ± 4.8 mL/s at 6 months after the procedure ( 37 , 41 ). However, no comparison with patients treated with other techniques has been performed, especially TURP, the most widely used surgical method and “gold standard” for BPH patients.…”
Section: Discussionmentioning
confidence: 89%
“…Researchers have verified transperineal percutaneous laser ablation (TPLA) a feasible and safe method (35)(36)(37)(38)(39)(40). Pacella CM conducted a single arm trial, performed the analysis on 160 patients with 6 months follow and 83 patients with 12 months after TPLA (41), and de Rienzo G conducted TPLA for 21 patients, verified the significant advantage in Qmax, IPSS, and peculiar ability to preserve ejaculation (38). However, high-quality RCTs, compared with TURP, the most widely used surgical method and "gold standard" for BPH patients, remained absent.…”
Section: Introductionmentioning
confidence: 99%
“…Several commercial software platforms have been developed to increase targeting accuracy that differ in both, technology (image acquisition and tracking mechanism) and biopsy route (transrectal or transperineal) [ 50 ]. TA is not routinely applied at prostate tissue, but experiences are increasing in this field, which represents a very promising field of application of TA for the future [ 56 , 57 ]. A case of biopsies of a prostatic nodule visible on MRI is shown in Figure 6 .…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Following on from Pacella' studies, laser ablation is today applied in the treatment of a variety of diseases, including not only liver and benign thyroid nodules, but also kidney, pancreatic and thyroid tumors and, most recently benign, and malignant prostate disease [7][8][9][10][11][12][13][14].…”
Section: Obituarymentioning
confidence: 99%
“…Even after his retirement, Dr. Pacella continued to assist colleagues and to participate in the scientific community providing exceptional insights into the potential of application of thermal ablations to the care of patients. In particular, in recent years, he developed a new technique for the treatment of benign prostatic adenomas, which with the application of laser through the transperineal route seems to provide a new minimally-invasive effective treatment strategy for patients [13,14]. Always extremely active and with an incredible amount of energy, he recently participated in the foundation of a study group on the application of minimallyinvasive treatments to the thyroid [15], and proposed to the international community a standardized terminology to be used in this field [16].…”
Section: Obituarymentioning
confidence: 99%